A new frontier in biostatistics: evaluating the accuracy of ChatGPT-4 vs. R in analysing liver resection data - Basel Jobeir; Abdulmajeed Alahdal; Fuat Saner; Sebastian Staubli; Dieter Broering; Dimitri Raptis (Journal of Global Health Economics and Policy)
# Background